1984
DOI: 10.1093/infdis/149.5.769
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic Characteristics of Isolates Associated with a New Epizootic of Raccoon Rabies in the United States

Abstract: A panel of 23 monoclonal antibodies to the nucleocapsid protein of rabies virus was used to study the antigenic character of isolates of rabies virus from raccoons in the mid-Atlantic region of the United States. Comparison of the reaction pattern of these isolates with that of isolates of rabies virus collected from areas of major rabies outbreaks (skunk rabies in the midwestern United States, fox rabies in the northeastern United States, and raccoon rabies in the southeastern United States) suggests that thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

1986
1986
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(36 citation statements)
references
References 9 publications
1
34
0
1
Order By: Relevance
“…This result is supported by molecular analysis that the deduced amino acid sequence of the N protein of the RC-HL strain exhibited 95-96% homology to that of other fixed rabies viruses (4). However, already established MAbs directed against N protein of rabies virus exhibited variable reactivity to street viruses from various geographic areas and animal species, despite a high degree of antigenic similarity among many fixed rabies viruses (14,16,20). MAbs obtained in the present study showed common reactivity to two street viruses, which were isolated from very different geographic regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is supported by molecular analysis that the deduced amino acid sequence of the N protein of the RC-HL strain exhibited 95-96% homology to that of other fixed rabies viruses (4). However, already established MAbs directed against N protein of rabies virus exhibited variable reactivity to street viruses from various geographic areas and animal species, despite a high degree of antigenic similarity among many fixed rabies viruses (14,16,20). MAbs obtained in the present study showed common reactivity to two street viruses, which were isolated from very different geographic regions.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, the antigenic organization of rabies virus N protein has been defined by the use of monoclonal antibodies (MAbs) (3,9,13,14,16 Slides were stored at -30 C until needed. Reactivity of MAbs to various rabies and rabies-related viruses in IFA was determined with FITCconjugated goat antibodies against mouse immunoglobulins (ICN, U.S.A.) as described previously (12).…”
mentioning
confidence: 99%
“…Local epizootics in little brown bats and big brown bats, should they occur, would be rare, short-lived events (Schowalter, 1980; Centers for Disease Control, 1983) and perhaps result from occasional interspecific transmission between colonial species and migratory solitary species. Smith et al (1984) report two different antigenic patterns in rabies isolates from big brown bats in Maryland. Different patterns of transmission (intraspecific and interspecific) may, in part, explain their results.…”
Section: N U M B E R T E S T E Dmentioning
confidence: 93%
“…The stocking rate and effort may be a factor in the level of genetic introgression (Buckmeier et al 2003). In addition to genetic effects, stocking or translocation of individuals may allow transmission of diseases to naïve populations, which can have devastating consequences for local populations, for example in USA raccoons (Smith et al 1984).…”
Section: Introductionmentioning
confidence: 99%